Cellulose-based magnetoelectric composites - Yan Zong; Tian Zheng; Pedro Martins; S. Lanceros-Mendez; Zhilian Yue; Michael J. Higgins (Nature Communications, 2017)
Magnetoelectric materials by converting a magnetic input to a voltage output holds promise in contactless electrodes that find applications from energy harvesting to sensing. Zong et al. report a promising laminate composite that combines a piezoelectric biopolymer, cellulose, and a magnetic material.